Care for bedridden patients, in Primary Health Care dentistry, in the peripheral region of São Paulo, Brazil - Bruno Lucena Antunes Abrante; Célia Regina Sanches; Luciana Munhoz; Henrique Aparecido Bueno da Silva; Josevan de Souza Silva; Cláudio Fróes de Freitas (Faculdade São Leopoldo Mandic, 2024)
ABSTRACT Objective: The objective is to describe the actions and activities carried out by the dentist during home visits. Methods: The experience took place during visits to users of the Basic Health Unit UBS Vila São Pedro in the Municipality of São Bernardo do Campo, a peripheral region with a lot of socioeconomic vulnerability, recording the periods from January to December 2022. The actions and activities described were cataloged as basic levels in health care: promotion, prevention, and diagnosis of soft tissue injuries and damage limitation. Dentists carried out 84 home visits with the purpose of offering oral health care to users restricted to bed, health promotion actions and activities were based on encouraging the practice of healthy habits, making caregivers of bedridden patients aware of the importance of oral hygiene, and how care should be carried out in the oral cavity of these patients where they no longer have the capacity for self-care. Results: The prevention actions were oral hygiene instruction mainly aimed at caring for patients who have restricted movements and who depend on a caregiver to perform oral hygiene, brushing or cleaning with gauze soaked with 0.12% chlorhexidine, and topical application of fluoride to the patients who still have dental elements. The other actions to limit pre-existing oral damage were tooth extractions with periodontal involvement. Conclusion: Therefore, dentist-in-home visits play a fundamental role in promoting quality of life and social life for patients who cannot go to a Basic Health Unit due to being temporarily restricted or permanently restricted to their home.